Correlation between Levels of Serum Amylase, Lipase and Triglyceride in Acute Pancreatitis Patients - Gunalan Govindarajan; Nina Tristina (Althea Medical Journal, 2015)
Background: Acute pancreatitis is an inflammation of pancreas associated with reversible pancreatic parenchymal injury. Studies in several countries indicate that the levels of amylase and lipase are usually elevated among patients with acute pancreatitis. Furthermore, hyperlipidemia, mainly high levels of triglycerides, may present in acute pancreatitis. The aim of this study was to determine the levels of serum amylase and lipase as well as their correlation with serum triglyceride level in acute pancreatitis patients.Methods: A retrospective study was conducted on medical records of 48 acute pancreatitis patients in Dr. Hasan Sadikin General Hospital Bandung, Indonesia from 2007to 2011. Data collected from the medical records were age, sex, levels of serum amylase, lipase and triglyceride. The distribution of data was determined using Shapiro-Wilk test. The correlation between serum pancreatic enzyme and triglyceride was analyzed using Spearman-rank test.Results: Most patients had increased levels of serum amylase and lipase in this study. However, no correlation between serum amylase and triglyceride (p-value = 0.312) was found. Furthermore, there was no correlation between serum lipase and triglyceride (p-value = 0.241).Conclusions: The levels of serum amylase and lipase increase in most patients with acute pancreatitis with no significant correlation between serum pancreatic enzymes (amylase and lipase) and triglyceride.Keywords: Acute pancreatitis, amylase, lipase, triglyceride DOI: 10.15850/amj.v2n1.420